O papel dos fundamentos domésticos na vulnerabilidade econômica dos emergentes - Ajax Moreira; Katia Rocha; Roberto Siqueira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2008)
– This study aims to evaluate policies that can potentially improve the economic vulnerability of a group of emerging market countries that comprises 23 countries in the period 1998-2007, coping up to 96% of the JPMorgan Emerging Markets Bond Index Global as of December 2007. Through a panel data model on sovereign spreads and based on the reasoning that the impact of a global risk aversion shock is country-specific, this study focuses on the role of the macroeconomic fundamentals as multipliers of external shocks. The results support policies towards financial liberalization, public debt management, fiscal policy sustainability, consistent economic growth, development of the domestic financial market, and improvements in governance indicators especially the rules of law and regulatory quality.
Keywords: E43; G15; F01; 330; Wirtschaftliche Anpassung; Schwellenländer